PMP (PMBOK4) - Baca, Claudia (Video mentor., 2012)
When it comes to passing the PMP certification exam, you’ll find no better resource than the PMP Video Mentor. You get video-based tutorials from one of the nation’s leading PMP instructors, Claudia M. Baca. Following the PMI’s curricula, the PMP Video Mentorhas everything you need to know to pass the PMP certification exam. Not only will you learn how to prepare for the exam, you will also get useful tips for completing and filing your paperwork, and discover useful things you should do on test day. Everything’s taught visually, using realistic project scenarios. You’ll master project initiation, planning, scoping, scheduling, budgeting, execution, monitoring and control, closing, quality, communications, procurement, PMI’s professional/social responsibility rules, and more. Learn at your pace, get the answers whenever you need them, and gain the confidence you need to ace the PMP certification exam! For all current and aspiring project managers who are preparing for the Project Management Institute’s PMP or CAPM online certification exam. Looking for a better way to master today’s rapidly changing technologies? Want expert help, but don't have the time or energy to read a book? Can't find classroom training worth the money? Discover Video Mentor: self-paced, personal video instruction from the world’s leading experts.